Epistemological foundations of social entrepreneurship from complex thinking - Soto, Fabiola Cruz Navarro; Castillo , Consuelo del Pilar Clemente; Chiparra , William Eduardo Mory; Casco , Roque Juan Espinoza; Sánchez, Aracelli del Carmen Gónzales; Quiñonez, Alberto Miguel Vizcarra; Ruiz, Lizet Malena Farro (Seven Editora, 2023)
The objective of the study was to establish a relationship between social entrepreneurship and the principles of complex thinking in Peru. The research was quantitative, and non-experimental, with a probability sample of 166 entrepreneurs (X = 55.4 years; 52% women). It was concluded that the structural models for the general objective and the specific objectives were acceptable (YB-X2/gl